PERUBAHAN TINGKAT SERAPAN NITROGEN, FOSFOR DAN KALIUM OLEH TANAMAN BAWANG MERAH LOKAL PALU AKIBAT PEMBERIAN EKSTRAK KOMPOS LIMBAH ORGANIK PASAR PADA ENTISOL POBOYA - Imam Wahyudi (Universitas Tadulako, 2013)
The infertile of Entisol, especially low availability of N, P, and K, causes the decreasing in growth and development of plant. Hence, important efforts on management of Entisol are the increasing in N, P, and K availability for crop demand. The extract of market organic residue compost is as source of organic matter used to improve the soil, although the fertilizers are still not yet have full attention. A study that was aimed to elucidate roles of the market organic residue compost extract on increasing N, P and K availability, improving crop growth and N, P, and K uptake by red onion Palu local variety in an Entisol was conducted in a glasshouse. Twelve treatments consisting of the fermentation duration and concentration of the extract, three rates of fermentation duration (4, 8 and 12 days), four rates of concentration of the extract (0, 5, 10, and 15 cc/L water) were arranged in a factorial randomized block design with three replicates. Results of the experiment showed that application of the extract concentration and fermentation duration significantly increased N, P, and K availability, improved plant growth and increased N, P and K taken up by the plant grown for 45 days. Key Words : Entisol, extract of compost, N, P, and K uptake